The Influence Of Leadership And Discipline On Employee Performance In The Bandar Lampung City Transportation Department - Emni, Ichsan Kamil; Ahirudin , Ahirudin (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2025)
The main support for achieving organizational goals is showing neatness and accuracy of work results without ignoring the volume of work, showing the large number of types of work carried out at one time so that efficiency and effectiveness can be carried out in accordance with the objectives, availability of employees to participate with other employees vertically and horizontally both inside and outside work so that work will get better, shows how much employees accept carrying out their work and taking responsibility for work results, and the initiative from within members of the organization to do work and solve problems at work without waiting for orders. One of the things that influences performance is leadership in an organization. The research objective in this thesis is to examine the influence of career development and work motivation on employee performance at the South Lampung Regional Development Planning Agency. This research uses a sampling research method with a total of 97 employees as respondents. Analysis was used using quantitative analysis and data processing using the SPSS program The research results show that leadership has a positive effect on employee performance with an influence contribution of 23.3%. Furthermore, discipline also has a positive effect on employee performance with an influence contribution of 13.8%. The regression test shows that together there is a positive influence between Leadership and Discipline on employee performance. The magnitude of the influence of the two variables X1 and X2 on Y is 24.8%, the remaining 75.2% is influenced by other variables outside this research.